2021
DOI: 10.1002/fsn3.2636
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militaris extract induces apoptosis and pyroptosis via caspase‐3/PARP/GSDME pathways in A549 cell line

Abstract: Cordyceps militaris (CM) is traditionally used as dietary therapy for lung cancer patients in China. CM extract (CME) is hydrosoluble fraction of CM and extensively investigated. Caspase‐3‐involved cell death is considered as its major anticancer mechanism but inconclusive. Therefore, we explore its caspase‐3‐dependent programmed cell death nature (apoptosis and pyroptosis) and validate its caspase‐3‐dependent property in loss‐of‐function experiment. Component profile of CME is detected by High Performance Liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 59 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…56,57 The caspase-3 apoptosis pathway plays a key role in apoptosis. 58 In the present study, immunofluorescence and Tunel assays showed that SeNPs-Met-MVs could significantly reduce the expression of apoptotic factors (cleaved caspase-3). At the same time, SeNPs-Met-MVs promoted the recovery of motor function in previous SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56,57 The caspase-3 apoptosis pathway plays a key role in apoptosis. 58 In the present study, immunofluorescence and Tunel assays showed that SeNPs-Met-MVs could significantly reduce the expression of apoptotic factors (cleaved caspase-3). At the same time, SeNPs-Met-MVs promoted the recovery of motor function in previous SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that oxidative stress ultimately leads to apoptosis of neuronal cells . The cysteine protease family is the primary regulator of apoptosis. , The caspase-3 apoptosis pathway plays a key role in apoptosis . In the present study, immunofluorescence and Tunel assays showed that SeNPs-Met-MVs could significantly reduce the expression of apoptotic factors (cleaved caspase-3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GSDME interacts physically with EGFR, covering the EGFRY1045 site and contributing to its stability [ 107 ]. The hydrosoluble fraction of cordyceps militaris extract (CME), a dietary herb for lung cancer patients, has been shown to induce A549 cell death by simultaneously activating caspase-3/GSDME pyroptotic pathways and caspase-3/PARP apoptotic pathways [ 108 ]. Yu et al revealed that the pyroptosis inhibitor (DSF) and apoptosis inhibitor (Z-VAD-FMK) prevented the cell mortality induced by nitidine chloride [ 109 ].…”
Section: Role Of Gsdme-mediated Pyroptosis In Cancer Therapymentioning
confidence: 99%
“…Also the newly discovered key protein of pyroptosis GSDME primarily relies on caspase-3 to mediate pyroptosis, and this pathway is of relevance especially in cancer. In the field of cancer treatment, chemotherapeutic drugs can mediate pyroptosis through the caspase-3/GSDME pathway, thereby enhancing the effect of chemotherapy; for instance, a Cordyceps militaris extract can induce caspase-3-dependent pyroptosis in A549 cells through caspase-3/PARP and caspase-3/GSDME pathways [ 45 ]. It has been reported that pathogenic Yersinia can lead to caspase-8-dependent pyroptosis after entering cells by inhibiting transforming growth factor β-activated kinase 1, activating and cleaving receptor-interacting protein kinase 1 [ 46 ] ( Figure 1 ).…”
Section: Pyroptosismentioning
confidence: 99%